CONTRIBUTION OF ELECTRICAL TOMOGRAPH AND SEISMIC REFRACTION IN SITE SELECTION FOR A DAM AT KOUNTOURA, CHANIA - Βαφείδης Α.; Hamdan, H.; Ανδρονικίδης Ν.; Δασύρας Α.; Κρητικάκης Γ.; Κουκαδάκη Μ.; Κουμάκης Ν.; Λαμπαθάκης Σ.; Μανούτσογλου Ε.; Οικονόμου Ν.; Παπακωνσταντίνου Κ.; Σπανουδάκης Ν. (Bulletin of the Geological Society of Greece, 2004)
This paper presents the results from a geophysical survey conducted at Kountoura vergion, Chania. The aim of this survey was to estimate the thickness of the geological formations in the area where a dam is going to be constructed. Electrical tomography and seismic refraction were utilized in order to indicate the location of four drill holes. VLF, well logging and drill hole sampling were carried out. A 3D model was constructed indicating the relief of the underlying neogene marls covered by recent deposits and neogene conglomerates whose thickness ranges from 2-30m. This model does not show any major faults, which may affect the construction of the dam. The relief of the neogene marls is mainly affected by the paleorelief of the phyllite-quartzites and the underlying carbonates. One of the wells shows the weathered layer of phylite-quartzites at depth less than 20 m. This survey shows that the geophysical method give useful information regarding the site selection for the dam at Kountoura.